Scientific and methodological principles of accounting, financial, informational and language and communication support for sustainable development of agribusiness entities and rural territories - (:unkn) unknown (Дніпровський державний аграрно-економічний університет, 2022)
The monograph examines the scientific problems of building accounting and financial support for sustainable development of agribusiness entities and rural areas. Modern information systems and technologies in accounting, auditing and taxation are considered. The theoretical, organizational and methodological principles of language and professional training of a specialist in agriculture, as well as modern technologies of education in higher educational institutions are revealed. The collective monograph was published within the framework of the State Budget research topics “Organizational and methodological principles of accounting, reporting and control in the system of economic stability of enterprises” (state registration number 0116U003135) and “Finance, banking system and insurance in integrated rural development” (state registration number 0119U001573), “Information technologies and mathematical methods for the development of the agricultural sector of the economy” (state registration number 0120U105338), “Language and professional training: linguistic, social, cognitive, communicative, cultural aspects” (state registration number 0116U005132). The publication is aimed at professionals engaged in practical activities in the field of regional policy, academics, government officials and the general public. У монографії досліджуються наукові проблеми побудови обліково-фінансового забезпечення сталого розвитку суб'єктів агробізнесу та сільських територій. Розглянуто сучасні інформаційні системи і технології в обліку, аудиті, оподаткуванні. Розкрито теоретико-організаційні та методичні основи мовно-професійної підготовки фахівця-аграрія, а також сучасні технології навчання у вищих навчальних закладах. Колективна монографія виконана в межах Держбюджетних тем дослідження «Організаційно-методичні засади обліку, звітності і контролю у системі забезпечення економічної стійкості підприємств» (державний реєстраційний номер 0116U003135) та теми «Фінанси. банківська система та страхування в умовах комплексного розвитку сільських територій» (державний реєстраційний номер 0119U001573), Інформаційні технології та математичні методи для розвитку аграрного сектору економіки (державний реєстраційний номер 0120U105338), Мовно-професійна підготовка фахівців: лінгвальний, соціальний, когнітивний, комунікативний, культурний аспекти (державний реєстраційний номер 0116U005132). Видання орієнтоване на фахівців, які займаються практичною діяльністю у сфері регіональної політики, академічних працівників, представників урядових кіл, широку громадськість.
Науково-методичні засади облікового, фінансового, інформаційного та мовно-комунікаційного забезпечення сталого розвитку суб'єктів агробізнесу та сільських територій
Keywords: accounting; облік; finance; фінанси; information; інформація; communication; комунікація; provision; забезпечення; розвиток; development; agribusiness; агробізнес